1
3(X + 4) + 7 = 7(X - 3) + 2
9.5
9(X - 3) + 3 = 4(X + 4) + 4
8.8
2
(X + 7) + 5 = 6(X - 4) + 2
6.8
6(X - 5) + 5 = (X + 6) + 6
7.4
3
(X + 8) + 4 = 5(X - 4) + 2
7.5
6(X - 5) + 6 = (X + 6) + 6
7.2
4
3(X + 6) + 7 = 8(X - 3) + 2
9.4
8(X - 3) + 3 = 2(X + 4) + 4
5.5
5
(X + 6) + 9 = 6(X - 6) + 2
9.8
6(X - 2) + 4 = (X + 2) + 2
2.4
6
(X + 6) + 1 = 7(X - 4) + 2
5.5
6(X - 3) + 4 = (X + 7) + 7
5.6
7
3(X + 4) + 8 = 8(X - 3) + 2
8.4
7(X - 2) + 4 = 2(X + 4) + 9
5.4
8
2(X + 8) + 9 = 8(X - 2) + 2
6.5
3(X - 3) + 4 = (X + 2) + 4
5.5
9
(X + 8) + 2 = 6(X - 4) + 2
6.4
6(X - 3) + 4 = 2(X + 6) + 4
7.5
10
(X + 5) + 6 = 6(X - 2) + 2
4.2
7(X - 5) + 3 = 2(X + 5)
8.4
11
(X + 2) + 3 = 3(X - 4) + 4
6.5
7(X - 2) + 3 = 3(X + 5)
6.5
12
3(X + 8) + 5 = 8(X - 2) + 2
8.6
3(X - 3) + 4 = (X + 3) + 5
6.5
13
(X + 5) + 3 = 6(X - 5) + 2
7.2
9(X - 2) + 4 = (X + 9) + 5
3.5
14
3(X + 9) + 6 = 8(X - 2) + 2
9.4
5(X - 6) + 3 = (X + 3)
7.5
15
(X + 2) + 9 = 5(X - 5) + 2
8.5
6(X - 5) + 4 = (X + 5) + 7
7.6
16
(X + 6) + 1 = 6(X - 2) + 2
3.4
7(X - 2) + 4 = 3(X + 2) + 6
5.5
17
(X + 7) + 8 = 3(X - 2) + 2
9.5
9(X - 3) + 4 = 4(X + 4) + 4
8.6
18
2(X + 3) + 2 = 7(X - 3) + 2
5.4
7(X - 5) + 4 = (X + 5) + 9
7.5
19
4(X + 2) + 9 = 9(X - 2) + 2
6.6
6(X - 3) + 4 = 2(X + 4) + 8
7.5
20
(X + 5) + 4 = 6(X - 2) + 2
3.8
5(X - 5) + 4 = (X + 4) + 5
7.5
21
3(X + 2) + 5 = 9(X - 4) + 2
7.5
8(X - 6) + 3 = 2(X + 6)
9.5
22
(X + 2) + 3 = 7(X - 6) + 2
7.5
9(X - 2) + 4 = 4(X + 3) + 7
6.6
23
2(X + 8) + 4 = 6(X - 2) + 2
7.5
8(X - 2) + 4 = 3(X + 5) + 2
5.8
24
2(X + 4) + 3 = 8(X - 6) + 2
9.5
8(X - 5) + 4 = 2(X + 6) + 9
9.5
25
2(X + 3) + 4 = 7(X - 4) + 2
7.2
7(X - 2) + 4 = 2(X + 5) + 9
5.8
26
(X + 9) + 7 = 6(X - 2) + 2
5.2
7(X - 6) + 4 = (X + 3) + 4
7.5
27
(X + 5) + 8 = 6(X - 5) + 2
8.2
7(X - 4) + 4 = 2(X + 9) + 7
9.8
28
3(X + 3) + 2 = 5(X - 2) + 2
9.5
6(X - 6) + 5 = (X + 7) + 9
9.4
29
(X + 4) + 9 = 5(X - 3) + 2
6.5
7(X - 3) + 5 = 2(X + 2) + 8
5.6
30
5(X + 2) + 3 = 9(X - 3) + 2
9.5
9(X - 7) + 5 = (X + 6) + 4
8.5
31
(X + 3) + 7 = 6(X - 6) + 3
8.6
9(X - 6) + 5 = (X + 7) + 4
7.5
32
2(X + 2) + 2 = 7(X - 3) + 3
4.8
9(X - 2) + 5 = (X + 7) + 8
3.5
33
3(X + 2) + 2 = 8(X - 4) + 3
7.4
7(X - 2) + 5 = 2(X + 5) + 3
4.4
34
(X + 6) + 1 = 3(X - 5) + 3
9.5
7(X - 6) + 5 = 2(X + 3) + 5
9.6
35
(X + 4) + 5 = 7(X - 3) + 3
4.5
5(X - 3) + 5 = (X + 7) + 9
6.5
36
4(X + 2) + 3 = 9(X - 4) + 3
8.8
8(X - 3) + 5 = 3(X + 5) + 8
8.4
37
2(X + 4) + 2 = 8(X - 4) + 3
6.5
9(X - 2) + 5 = 4(X + 3) + 9
6.8
38
(X + 8) + 6 = 5(X - 3) + 3
6.5
6(X - 4) + 5 = (X + 9) + 6
6.8
39
2(X + 7) + 6 = 7(X - 3) + 3
7.6
8(X - 5) + 5 = 3(X + 2) + 3
8.8
40
(X + 2) + 6 = 9(X - 7) + 3
8.5
8(X - 2) + 5 = 4(X + 4) + 3
7.5
41
(X + 7) + 4 = 9(X - 4) + 3
5.5
6(X - 2) + 5 = (X + 7) + 9
4.6
42
2(X + 5) + 3 = 6(X - 4) + 3
8.5
7(X - 4) + 5 = 3(X + 2) + 5
8.5
43
2(X + 3) + 1 = 6(X - 3) + 3
5.5
8(X - 3) + 5 = 3(X + 3) + 4
6.4
44
2(X + 6) + 5 = 6(X - 4) + 3
9.5
7(X - 3) + 5 = 2(X + 3) + 2
4.8
45
3(X + 2) + 7 = 7(X - 4) + 3
9.5
6(X - 4) + 5 = 2(X + 2) + 3
6.5
46
(X + 8) + 6 = 6(X - 6) + 3
9.4
7(X - 3) + 5 = 3(X + 4) + 6
8.5
47
(X + 4) + 4 = 5(X - 5) + 3
7.5
6(X - 6) + 5 = (X + 6) + 2
7.8
48
3(X + 2) + 9 = 8(X - 3) + 3
7.2
6(X - 5) + 5 = (X + 2) + 9
7.2
49
3(X + 2) + 6 = 8(X - 5) + 3
9.8
6(X - 5) + 4 = (X + 7)
6.6
50
(X + 2) + 2 = 6(X - 6) + 3
7.4
6(X - 6) + 4 = (X + 5)
7.4
51
(X + 2) + 4 = 5(X - 3) + 3
4.5
8(X - 2) + 5 = 4(X + 3) + 7
7.5
©Ms. Garcia Math
Name:
ID:
Quiz:
Grade
Solving Equations with Variables on Both Sides
?
Distribute
Find the smaller variable term.
Subtract it from both sides.
Solve for X.
Solve for the variable shown in the expression
1)
X =
2)
X =
3)
X =
4)
X =
5)
X =